The Beneficial Role of Sirtuin 1 in Preventive or Therapeutic Options of Neurodegenerative Diseases. (10th November 2022) - Liu, Haihui; Xu, Si; Wang, Chen; Deng, Yu; Xu, Bin; Yang, Tianyao; Sun, Jingyi; Liu, Wei
Highlights: SIRT1 is involved in the pathological process of NDDs. SIRT1-mediated biological effects are related to NDDs. SIRT1 provides new targets for the preventive or treatment of NDDs. Abstract: Sirtuin 1 (SIRT1) is an NAD + dependent deacetylase that modify the gene expression through histone deacetylation. SIRT1 plays a crucial role in regulating a wide range of physiological processes by adjustment multiple mechanisms through the deacetylation of multiple substrates. Neurodegenerative diseases are a series of chronic diseases characterized by dysfunction and loss of neurons. Its basic pathogenesis is filamentous tangles and amyloid deposits, such as Amyloid-β (Aβ), tau protein, α-synuclein, including Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD). This summarizes introduces the structure and function of SIRT1, and then analyzes the protective effects of SIRT1 on neurological diseases by regulating circadian rhythm, aging, oxidative stress, mitochondrial dysfunction and neuroinflammation related pathways.